Practice of Principal Academic Supervision in Improving the Quality of Teacher Learning at JHS 25 Padang - Arin, Yudela; Yolanda, Septiara; Revita, Yuni; Marsidin, Syufyarma; Rifma, Rifma (International Journal of Educational Dynamics, 2023)
One important program that must be implemented in principle in teacher training to improve the quality of learning is the supervision of school principals in improving the quality of teacher learning. The purpose of this research is to learn about supervision actions or practices carried out by principals in schools to improve the quality of teacher learning. This research is expected to be able to assist school principals in improving the quality of learning through teacher supervision. Improving the quality of teacher learning will have a good influence on students, thereby increasing the quality of education. However, the problem is that the supervision of school principals is still underutilized, which will have a negative impact on improving the quality of learning. The method used in this study uses a qualitative approach with a descriptive approach. Research instruments include observations, questionnaires, interviews, and documentation. Principals and teachers became the focus of the investigation. Based on research findings, the practice of supervising school principals in improving the quality of learning at SMP 25 Negeri Padang is not optimal. This cannot be ignored because if this is not addressed immediately, it will have a negative impact on student learning. parties hope that this research will continue.